2018
DOI: 10.1021/jacs.8b05220
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy to Synthesize Molecular Knots and Links Using the Hydrophobic Effect

Abstract: Conventional approaches to the synthesis of molecular knots and links mostly rely on metal templation. We present here an alternative strategy that uses the hydrophobic effect to drive the formation of complex interlocked structures in water. We designed an aqueous dynamic combinatorial system that can generate knots and links. In this system, the self-assembly of a topologically complex macrocycle is thermodynamically favored only if an optimum packing of all its components minimizes the hydrophobic surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
91
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 60 publications
2
91
0
3
Order By: Relevance
“…Both conformations are in slow exchange,a si ndicated by the presence of exchange cross-peaks between 1 and 2 in the 2D NOESY spectrum ( Figure S5). [7] In this conformation, the broader range of aromatic-proton chemical shifts (d % 4-11 ppm) and the notable shielding of the isophthalic proton (k; d < 4ppm) reflect ac ompact stacking of all aromatic units. The 1 HNMR features of 2 perfectly coincide with those recorded in pure D 2 O.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both conformations are in slow exchange,a si ndicated by the presence of exchange cross-peaks between 1 and 2 in the 2D NOESY spectrum ( Figure S5). [7] In this conformation, the broader range of aromatic-proton chemical shifts (d % 4-11 ppm) and the notable shielding of the isophthalic proton (k; d < 4ppm) reflect ac ompact stacking of all aromatic units. The 1 HNMR features of 2 perfectly coincide with those recorded in pure D 2 O.…”
mentioning
confidence: 98%
“…[7] Its 1 HNMR characterization, performed in D 2 O, previously demonstrated that SL was made of four interlocked arms,each constituted of an isophthalic moiety linked with hydrazone bonds to two quinolinium units.W epursued further analyses with the aim to gain additional structural information. [7] Its 1 HNMR characterization, performed in D 2 O, previously demonstrated that SL was made of four interlocked arms,each constituted of an isophthalic moiety linked with hydrazone bonds to two quinolinium units.W epursued further analyses with the aim to gain additional structural information.…”
mentioning
confidence: 99%
“…As ac onsequence, avariety of complex molecules [9][10][11][12][13] are obtained in high yields, especially when these self-assembled molecules are sophisticatedly designed to represent the most thermodynamically favoured products.One of the major disadvantages of iminebased DCC is that, this dynamic bond is apt to undergo hydrolysis in aqueous solution. Avariety of macrocycles, [15,16] cages, [17] catenanes [18,19] as well as knots [20] were obtained in water based on hydrazone condensation in pure water. Thepartially negatively-charged carbon atom is therefore less electrophilic,p rotecting the C=Nb ond from nucleophilic attack by water molecules or other nucleophiles.…”
mentioning
confidence: 99%
“…Therefore,the self-assembled products containing imine can hardly realize their functions in water, the medium of life.H ydrazone (-C=NÀN-), [14] am ore robust counterpart of imine,w as thus employed to develop water-compatible DCC approaches.T he higher stability of hydrazone results from the delocalization of the lone electron pair in the adjacent nitrogen atom onto to the C = Nd ouble bond, resulting in acharge-separated resonance form, namely -C À ÀN=N + -. Avariety of macrocycles, [15,16] cages, [17] catenanes [18,19] as well as knots [20] were obtained in water based on hydrazone condensation in pure water. Avariety of macrocycles, [15,16] cages, [17] catenanes [18,19] as well as knots [20] were obtained in water based on hydrazone condensation in pure water.…”
mentioning
confidence: 99%
“…Controlling of chemical reactions by non-covalent or weak interactions are gaining significant interests.T om ake newer or functional materials on demanda ppropriate interactions like halogenb onding, [30] charge-transfer, [31] hydrophobic effect, [32] cation-p, [33] anion-p, [34] etc. are generallyu sed routinely.…”
mentioning
confidence: 99%